Deteksi Gen Penyandi Resistensi ampC dan mcr-1 pada Escherichia coli penyebab Colibacillosis Unggas di Sukabumi (DETECTION OF GENE ENCODING RESISTANCE AMPC AND MCR-1 IN ESCHERICHIA COLI CAUSES AVIAN COLIBACILLOSIS IN SUKABUMI) - Indrawati, Agustin; Kurnia, Ryan Septa; Mayasari, Ni Luh Putu Ika (Jurnal Veteriner; Vol 20 No 4 (2019), 2019)
Antibiotic resistance has become a global problem that can threaten human and animal health. The use of antibiotics in livestock as a treatment and control of disease is often associated with the cause of the spread of resistant bacteria. Resistance bacteria are caused by presence of resistant gene resistance that can move between bacteria. This study aims to detect the presence of genes that encode resistance to ampicillin (ampC) antibiotics and colistin (mcr-1) in Escherichia coli bacteria derived from cases of colibacillosis in Sukabumi. A total of 25 isolates of E. coli archive collection of PT. Medika Animal Lab is used in this research. All isolates identified using PCR were then tested for sensitivity using the disk diffusion method and minimum inhibitory concentrations (MICs). Isolates that are resistant to ampicillin and colistin were tested for detection of ampC and mcr-1 genes using PCR. The results of the sensitivity test showed the whole isolates were resistant to ampicillin (100%) and phosphomycin (8%), but none were resistant to colistin sulphate. The total isolate E. coli successfully detected gene encoding resistance of ampC (100%). The results of sensitivity and resistance detection test showed that the whole isolates were ampicillin resistant and had the ampC resistance-encoding gene.